a) x^2+x=2x+2 b) (x-1)^2=2(x^2-1) c) 2(x+2)^2-x^3-8=0

a) x^2+x=2x+2
b) (x-1)^2=2(x^2-1)
c) 2(x+2)^2-x^3-8=0

2 bình luận về “a) x^2+x=2x+2 b) (x-1)^2=2(x^2-1) c) 2(x+2)^2-x^3-8=0”

  1. a) $x$ $×$ $2$ $+$ $x$ $=$ $2x$ $+$ $2$
        $2x$ $+$ $x$ $-$ $2x$ $-$ $2$ $=$ $0$
        $x$ $-$ $2$ $=$ $0$
        $x$ $=$ $2$
    Vậy tập nghiệm của phương trình là: $S$ $=${ 2 }
    b) $(x – 1)$ $×$ $2$ $=$ $2$ $×$ $(x × 2 – 1)$
         $2x$ $-$ $2$ $=$ $4x$ $-$ $2$
         $2x$ $-$ $2$ $-$ $4x$ $+$ $2$ $=$ $0$
        $-2x$ $=$ $0$
         $x$ $=$ $0$
    Vậy tập nghiệm của phương trình là: $S$ $=${ 0 }
    c) $2×$ $(x  +2)$ $×$ $2$ $-$ $x$ $×$ $3$ $-$ $8$ $=$ $0$
        $4x$ $+$ $8$ $-$ $3x$ $-$ $8$ $=$ $0$
        $x$ $=$ $0$
    Vậy tập nghiệm của phương trình là: $S$ $=${ 0 }

    Trả lời
  2. a, x^2+x=2x+2
    ⇒x^2+x-2x-2=0
    ⇒x(x+1)-2(x+1)=0
    ⇒(x+1)(x-2)=0
    ⇒$\left[\begin{matrix} x+1=0\\ x-2=0\end{matrix}\right.$
    ⇒$\left[\begin{matrix} x=-1\\ x=2\end{matrix}\right.$
    Vậy x in {-1;2}
    b, (x-1)^2=2(x^2-1)
    ⇒x^2-2x+1=2x^2-2
    ⇒x^2-2x+1-2x^2+2=0
    ⇒-(x^2+2x-3)=0
    ⇒x^2+2x-3=0
    ⇒x^2-x+3x-3=0
    ⇒x(x-1)+3(x-1)=0
    ⇒(x-1)(x+3)=0
    ⇒$\left[\begin{matrix} x-1=0\\ x+3=0\end{matrix}\right.$
    ⇒$\left[\begin{matrix} x=1\\ x=-3\end{matrix}\right.$
    Vậy x in {-3;1}
    c, 2(x+2)^2-x^3-8=0
    ⇒2(x+2)^2-(x^3+8)=0
    ⇒2(x+2)^2-(x+2)(x^2-2x+4)=0
    ⇒(x+2)(2x+4-x^2+2x-4)=0
    ⇒(x+2)(-x^2+4x)=0
    ⇒-x(x+2)(x-4)=0
    ⇒$\left[\begin{matrix} x=0\\ x+2=0\\x-4=0\end{matrix}\right.$
    ⇒$\left[\begin{matrix} x=0\\ x=-2\\x=4\end{matrix}\right.$
    Vậy x in {-2;0;4}

    Trả lời

Viết một bình luận

Câu hỏi mới